2016
DOI: 10.3791/54409
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Homogeneous MALDI Samples for Quantitative Applications

Abstract: This protocol demonstrates a simple sample preparation to reduce spatial heterogeneity in ion signals during matrix-assisted laser desorption/ionization (MALDI) mass spectrometry. The heterogeneity of ion signals is a severe problem in MALDI, which results in poor data reproducibility and makes MALDI unsuitable for quantitative analysis. By regulating sample plate temperature during sample preparation, thermal-induced hydrodynamic flows inside droplets of sample solution are able to reduce the heterogeneity pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Despite many developments, quantification in MSI is still challenging. A key factor to account for, in order to quantify MSI results, is ion suppression. , Especially in a heterogeneous tissue like the intestine where there are not only different tissue types but also a large proportion of lumen where the analyte-to-MALDI matrix ratio is very different compared to the tissue, the ion suppression effect can vary greatly between the different areas. Therefore, more conventional methods like spotting a dilution series onto the control tissue or the mimetic tissue model where a dilution series is prepared in tissue homogenate will not provide accurate data.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many developments, quantification in MSI is still challenging. A key factor to account for, in order to quantify MSI results, is ion suppression. , Especially in a heterogeneous tissue like the intestine where there are not only different tissue types but also a large proportion of lumen where the analyte-to-MALDI matrix ratio is very different compared to the tissue, the ion suppression effect can vary greatly between the different areas. Therefore, more conventional methods like spotting a dilution series onto the control tissue or the mimetic tissue model where a dilution series is prepared in tissue homogenate will not provide accurate data.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of homogeneous target surfaces is of importance for successful quantitative measurements by MALDI. Ou et al (2016) have demonstrated the preparation of homogeneous MALDI samples for quantitative applications by regulation of the sample plate temperature during sample preparation.…”
Section: Quantificationmentioning
confidence: 99%
“…In order to perform a quantitative analysis with the highest possible accuracy, it is important to find the optimal sample preparation method and to perform standard calibrations. Many sample preparation methods have been reported for improving the quality of sample deposition and obtaining fine and uniform crystals: Rapid or slow evaporation [ 5 , 6 ], seeded layers [ 7 ], sandwiches [ 8 ], and electrospray deposition [ 9 ], for example. The chosen method depends on the nature of the target molecules, the instrument used, the MS method applied, and the degree of precision required to answer the analytical question.…”
Section: Introductionmentioning
confidence: 99%